Foreign acquisitions – A shortcut to higher productivity and expansion in smaller firms? - Kent Eliasson; Pär Hansson; Markus Lindvert (Örebro University School of Business, 2020)
The purpose of this paper is to analyze the effects of foreign acquisitions on the productivity of acquired Swedish firms. However, because an acquisition is an opportunity to restructure a business and because such changes, in turn, can result in increased productivity, the effects may be observed in other outcome variables. Therefore, we also study the effects after an acquisition on employment, share of skilled labor, and export and import intensities in Swedish firms taken over by foreign multinationals (MNEs). As we examine the effects on both acquired manufacturing and service firms, we also analyze the effects in small firms, e.g., those with one or more employees. To control for the possible endogeneity of foreign direct investment decisions, propensity score matching is combined with a difference-in-difference approach. The positive effects on productivity, the share of skilled labor, employment and the export and import intensities of foreign acquisitions are most pronounced among small service firms. We also find positive productivity effects of foreign acquisitions in large manufacturing firms. A contributing factor is the investment in human capital, i.e., increasing the share of skilled labor. Foreign acquisitions appear to involve expansion in the acquired firms, particularly with respect to employment increases in small firms. Thus, being acquired by a foreign MNE appears to be a conceivable alternative for small firms with strong future growth potential, especially when dealing with the growth barriers that such firms usually encounter.
Keywords: D22; F21; F23; J24; 330; foreign acquisition; restructuring; cherry-picking; labor productivity; skilled labor; export and import intensities